Pengaruh Kenaikan Tarif PPN 11% Terhadap Kinerja Keuangan Pada Perusahaan Retail Go Public Di Bursa Efek Indonesia Tahun Pajak 2023 - Zawitri, Sari; Yuliana, Elsa Sari; Kurniasih, Ninik (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This study aims to analyze the impact of government regulations regarding the increase in Value Added Tax (VAT) by 11% as a response to post-COVID-19 economic recovery and budget deficit reduction. The VAT increase potentially raises the prices of essential goods, affecting companies' financial performance. The primary focus of this research is on profitability ratios, including Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Additionally, the analysis includes the Debt to Equity Ratio (DER) and Price Earnings Ratio (PER) for publicly listed companies on the Indonesia Stock Exchange (IDX). The population of this study comprises the 32 largest retail companies on the IDX in 2023. This research tests six hypotheses concerning changes in financial performance before and after the implementation of the 11% VAT increase, evaluating a two-year period (2022 and 2023). The method used is the Paired Sample T-test with SPSS version 26. The results show an increase in GPM and NPM, but no significant differences in ROA and DER. Conversely, PER shows a drastic decline. This research is expected to serve as an important reference in the field of accounting, particularly related to tax obligations for corporate taxpayers following the VAT increase. Keywords: Profitability Ratios, Value Added Tax (VAT), Retail Sector, T-test.